Non-Competing Groups - Davenport, H. J. (Quarterly Journal of Economics, 1925)
Values reporting themselves as relative prices, costs, to bear on values, must be relative costs, and must be reduced to money terms, 52. — Efforts and waitings, therefore, articulate with prices only when translated into money costs, 54. — The employer vs. employee point of view, 55. — The assumption that, in general, wages and interest are proportional with effort and waiting sacrifices, 55. — Cairnes's interpretation, with wages and interest conceived as derivative from product prices, and with labor as the antithesis of the remuneration of it, 55. — Employer vs. employee cost, 56. — Relation of effort and waitings costs to employer money costs, 56. — Mill, 56. — Taussig and Marshall, 57. — Ricardo, 59. — Ricardo and Cairnes, 59. — The constitution of the groups — by definition, 63. — The groupings not by vocations but by remunerations, 65. — In what sense can the intra-group relationships be competitive? 66. — Cairnes's and Taussig's reports of the groupings, 67. — Dates of group fixation vs. dates of group competition, 70. — The groupings further examined, 71. — Social stratification the point of emphasis, not competition or the lack of it, 73. — Inherited opportunity never more than part explanation of income groupings, or of ratios of income to sacrifice, 74. — Complete fluidity of labor also would leave the groupings no less inadequate, 76. — The three requisites for a tenable labor theory of values still unmet, 80.